High-temperature wear-resistant composite coating, preparation method, steel part and application of steel part

By using TiCN powder and Re2O3 powder in the high-temperature wear-resistant composite coating, combined with metal powder, and using laser cladding technology to prepare the coating, the problem of insufficient wear resistance and oxidation resistance of the existing coating under high-temperature conditions is solved, and a significant improvement in high-temperature wear resistance and oxidation resistance is achieved.

CN119640261APending Publication Date: 2025-03-18CHINA INNOVATION ACADEMY OF INTELLIGENT EQUIP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411921585.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing high-temperature wear-resistant composite coatings are prone to cracks and pores during the preparation process, resulting in insufficient wear and oxidation resistance of the coating, which limits its application in high-temperature operating conditions.

Method used

TiCN powder and Re2O3 powder are used as main components, combined with metal powder, and high-temperature wear-resistant composite coating is prepared on the surface of the matrix through laser cladding technology to form a γ-Co solid solution with a face-centered cubic structure as the matrix phase, containing the microstructure of intermetallic compounds.

Benefits of technology

It significantly improves the high-temperature wear resistance and high-temperature oxidation resistance of the substrate surface, reduces the pores and cracks of the coating, and forms a dense and fine grain structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640261A_ABST
    Figure CN119640261A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature wear-resistant composite coating, a preparation method, a steel part and application of the high-temperature wear-resistant composite coating, and the high-temperature wear-resistant composite coating is prepared from the following raw materials in percentage by weight: 5-10% of TiCN powder, 0.3-0.8% of Re2O3 powder and the balance of metal powder, according to the microstructure of the high-temperature wear-resistant composite coating, a gamma-Co solid solution of a face-centered cubic structure serves as a matrix phase, and intermetallic compounds Co3W, FeCo2, FeCo5, (Cr, Fe) 7C3 and Cr3C2 and part of elements Mo, W and Ni are distributed in the matrix phase in a dispersed mode. The high-temperature wear-resistant composite coating which is free of pores and cracks, compact in structure and fine in grain can be prepared on the surface of the matrix by adopting a cladding process, and the high-temperature wear resistance and the high-temperature oxidation resistance of the surface of the matrix are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of metallurgical technology, and in particular to a high-temperature wear-resistant composite coating and a preparation method thereof, a steel part and applications thereof. Background Art

[0002] Metals such as steel are widely used in industrial production, but they will wear out under high temperature conditions and fatigue failure is common, which greatly affects production safety and seriously damages economic benefits.

[0003] Some literature has proposed a method for preparing stellite6 composite coating by laser cladding on H13 steel surface. Since direct cladding will produce cracks, multiple materials are used as transition layers. Since the preparation process of gradient coating is relatively complicated and the thickness of each layer is difficult to control, the use conditions of the coating are greatly limited. Some literature has also proposed adding WC ceramic powder to stellite6 powder and CeO 2 As a modifier, WC was added to the cladding powder and a coating was prepared on the surface of 42CrMo steel plate. Although the wear resistance and corrosion resistance were improved, the addition of a large amount of WC ceramic particles would cause greater stress in the cladding process. 2 As a modifier, it weakens the interfacial energy of WC particles, but the coating still has a high tendency to crack. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a high-temperature wear-resistant composite coating and a preparation method, a steel part and its application.

[0005] The present invention solves the technical problem by adopting the following technical solutions.

[0006] The present invention provides a high temperature wear-resistant composite coating. The raw materials for preparing the high temperature wear-resistant composite coating include, by weight percentage: 5%-10% of TiCN powder and Re 2 O 3 The powder is 0.3%-0.8%, and the balance is metal powder. The microstructure of the high temperature wear-resistant composite coating is: a face-centered cubic structure of γ-Co solid solution as the matrix phase, and intermetallic compounds Co are dispersed in the matrix phase. 3 W, FeCo 2 、FeCo 5 、(Cr,Fe) 7 C 3 and Cr 3 C 2 And some elements Mo, W and Ni.

[0007] The present invention provides a method for preparing a high-temperature wear-resistant composite coating, which comprises: providing a substrate, and applying the high-temperature wear-resistant composite coating on the surface of the substrate.

[0008] The present invention provides a steel part, which is obtained by laser cladding a high-temperature wear-resistant composite coating on the surface of a steel substrate using the above-mentioned preparation method.

[0009] The present invention provides an application of the above-mentioned steel part in preparing a hot forging die.

[0010] The present invention has the following beneficial effects:

[0011] The present invention provides a high temperature wear-resistant composite coating and a preparation method, a steel part and an application thereof. The raw materials for preparing the high temperature wear-resistant composite coating provided by the present invention include, by weight percentage, 5%-10% TiCN powder and Re 2 O 3 The powder is 0.3%-0.8%, and the balance is metal powder. The microstructure of the high temperature wear-resistant composite coating is: a face-centered cubic structure of γ-Co solid solution as the matrix phase, and intermetallic compounds Co are dispersed in the matrix phase. 3 W, FeCo 2 、FeCo 5 、(Cr,Fe) 7 C 3 and Cr 3 C 2 and some elements Mo, W and Ni, and the above-mentioned raw materials are used to apply a high-temperature wear-resistant composite coating with no pores and cracks, dense structure and fine grains on the surface of the substrate, which can significantly improve the high-temperature wear resistance and high-temperature oxidation resistance of the substrate surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0013] Figure 1 Scanning electron microscope image of the cladding powder used in Example 1;

[0014] Figure 2 Electron microscope images of the cladding layer on the surface of the sample in Example 1 (Figure a) and Comparative Example 1 (Figure b);

[0015] Figure 3 Comparison of wear amounts of different embodiments 1-3, comparative examples 1-3 and substrate;

[0016] Figure 4 Comparison chart of oxidation weight gain of different Examples 1-3, Comparative Examples 1-3 and substrate;

[0017] Figure 5 Optical microscopic images of the cladding layer on the surface of the samples in Example 1 (Figure a) and Comparative Example 6 (Figure b). DETAILED DESCRIPTION

[0018] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0019] A high temperature wear-resistant composite coating and a preparation method, a steel part and applications thereof provided in an embodiment of the present invention are described in detail below.

[0020] In a first aspect, an embodiment of the present invention provides a high temperature wear-resistant composite coating, wherein the raw materials for preparing the high temperature wear-resistant composite coating include, by weight percentage: 5%-10% TiCN powder and Re 2 O 3 The powder is 0.3%-0.8%, and the balance is metal powder. The microstructure of the high temperature wear-resistant composite coating is: a face-centered cubic structure of γ-Co solid solution as the matrix phase, and intermetallic compounds Co are dispersed in the matrix phase. 3 W, FeCo 2 、FeCo 5 、(Cr,Fe) 7 C 3 and Cr 3 C 2 And some elements Mo, W and Ni.

[0021] The present invention provides a high temperature wear-resistant composite coating, the raw materials for its preparation include: 5%-10% TiCN powder and Re 2 O 3 Powder 0.3%-0.8%, the rest is metal powder. Among them: metal powder such as cobalt-based alloy powder has good self-deoxidation and slag-making properties, which helps to obtain a cladding layer with low oxide content and low porosity. Its excellent wettability has a favorable effect on the fluidity and surface tension of the alloy; TiCN powder has the advantages of both TiC and TiN materials, such as high melting point, high hardness, wear resistance, thermal stability, as well as good wettability, electrical and thermal conductivity, chemical stability and biocompatibility; Re 2 O 3The powder will purify the cladding layer during the cladding process. The rare earth elements added to the cladding layer will have dispersion strengthening and solid solution strengthening effects on the cladding layer, which can effectively reduce the defects in the cladding layer and obtain good organization and performance. The high-temperature wear-resistant composite coating prepared using the above-mentioned raw materials has the following microstructure: a face-centered cubic γ-Co solid solution is used as the matrix phase, and the intermetallic compound Co is dispersed in the matrix phase. 3 W, FeCo 2 、FeCo 5 、(Cr,Fe) 7 C 3 and Cr 3 C 2 and some elements Mo, W and Ni, and has the following macroscopic performance: no pores and cracks, dense structure, fine grains. Applying the above high temperature wear-resistant composite coating on a substrate such as a steel part can effectively improve the high temperature wear resistance and high temperature oxidation resistance of the steel part surface.

[0022] In some optional embodiments, Re 2 O 3 The Re in the powder includes one or more of Y, La, and Ce, and the metal powder is Stellite 6 powder.

[0023] In some optional embodiments, the raw materials for preparing the high temperature wear-resistant composite coating include, by weight percentage: 5%-10% TiCN ceramic powder and Y 2 O 3 Rare earth powder 0.3%-0.8%, the rest is stellite6 alloy powder. After the above three powders are mixed, nano-scale TiCN ceramic powder and Re 2 O 3 Rare earth powder is dispersed on the surface of stellite 6 alloy powder particles. It can act as a heterogeneous nucleating agent in the coating preparation process, reduce the nucleation barrier, promote the transformation of grain growth from columnar crystal growth to equiaxed crystal growth, and reduce crack generation.

[0024] In some optional embodiments, the particle size of the stellite6 alloy powder is 45-105 μm, and the chemical composition is as follows: C: 1.3%, Ni: 2%, W: 4.5%, Si: 0.8%, Mn: 0.5%, Mo: 1%, Fe: 2%, Cr: 29.7%, Co: balance; the particle size of the TiCN ceramic powder is 100-500 nm, and the chemical composition is as follows: Fe: 0.1%, TiCN: balance; Y 2 O 3 The particle size of rare earth powder is 100-500nm, and the chemical composition is as follows: Fe 2 O 3 : 0.001%, Y2 O 3 :margin.

[0025] In a second aspect, an embodiment of the present invention provides a method for preparing a high-temperature wear-resistant composite coating, which comprises: providing a substrate, and applying the above-mentioned high-temperature wear-resistant composite coating on the surface of the substrate.

[0026] In some optional embodiments, a high temperature wear-resistant composite coating is applied on the substrate surface by laser cladding, wherein: the laser power is controlled to be 2000-3500W, the scanning speed is 40-60mm / s, the overlap rate is 50-70%, the spot diameter is 3.5-4mm, the powder feeding rate is 35-50g / min, and the shielding gas flow rate is 13-20L / min, preferably the shielding gas is an inert gas. When applying the coating on the substrate surface, the laser power, scanning speed, overlap rate, spot diameter, powder feeding rate and shielding gas flow of the cladding process are controlled within a suitable range, and a coating with no pores and cracks, dense structure and fine grains can be prepared. If the laser power is low and the scanning speed is too high, the elements in the alloy powder will not have time to be uniformly heated and melted. In addition, under the condition of rapid cooling and solidification, the melted elements will not have time to produce uniform heat diffusion, and a continuous and smooth cladding layer surface cannot be formed. If the laser power is too high, the dilution rate will be too large to affect the coating performance.

[0027] The embodiment of the present invention provides a method for preparing a high temperature wear-resistant composite coating, which uses the following raw materials (also referred to as cladding powder): by weight percentage: 5%-10% TiCN powder and Re 2 O 3 The powder is 0.3%-0.8%, and the rest is metal powder. A high-temperature wear-resistant composite coating (also called a cladding layer) is applied on the substrate surface by laser cladding. During the laser cladding process, the carbides precipitated after the metal powder such as stellite6 metal powder is added to the TiCN ceramic particles inhibit the growth of the bonding phase γ-Co metal grains; secondly, the nano-scale TiCN ceramics coated on the surface of the alloy powder and Re 2 O 3 Rare earth particles can act as heterogeneous nucleating agents during the solidification process, reduce the nucleation barrier, and promote the transformation of grain growth from columnar crystal growth to equiaxed crystal growth, thereby effectively inhibiting cracks and forming a relatively fine and dense cladding layer. At the same time, the high-temperature wear resistance of the cladding layer depends on the type of cladding alloy matrix structure and the size, quantity, and distribution state of the precipitated second phase. On the one hand, in addition to the nano-ceramic strengthening phase of TiCN itself, the Co 3 W, FeCo 2 、FeCo 5 、(Cr,Fe) 7 C 3 and Cr3 C 2 And some elements Mo, W and Ni, these solid solution phases can form solid solution strengthening, carbides can form hard phases, which can significantly improve the microhardness and wear resistance of the cladding layer, reduce the probability of scrapping due to friction and wear during use, and further extend the service life. Secondly, dense organizational structure and low porosity are also important factors in improving the high-temperature wear resistance of the coating. On the other hand, the Cr element in the stellite6 alloy powder forms Cr 2 O 3 The protective film effectively prevents the penetration of O element into the coating and has good high temperature oxidation resistance.

[0028] In some optional embodiments, before applying the high-temperature wear-resistant composite coating to the substrate, the substrate surface needs to be polished with sandpaper to remove surface stains, and cleaned with anhydrous ethanol and blown dry.

[0029] In some optional embodiments, the substrate is a metal material, including at least one of hot working die steel, cold working die steel, high speed tool steel, high chromium cast iron, stainless steel, heat-resistant steel, wear-resistant and corrosion-resistant ferrous metal materials, non-ferrous metal materials, and self-fluxing alloys, preferably hot working die steel, and more preferably H13 steel.

[0030] In some optional embodiments, the thickness of the high temperature wear-resistant composite coating is 1-2 mm.

[0031] In a third aspect, an embodiment of the present invention provides a steel part obtained by laser cladding a high-temperature wear-resistant composite coating on the surface of a steel substrate using the above-mentioned preparation method.

[0032] In a fourth aspect, an embodiment of the present invention provides a use of the above-mentioned steel part in preparing a hot forging die.

[0033] The present invention will be further described below in conjunction with the embodiments.

[0034] The method for testing the high temperature wear resistance and high temperature oxidation resistance of the cladding layer in the following examples and comparative examples is as follows:

[0035] The high temperature friction and wear test was carried out on a HT-1000 high temperature friction and wear tester. 3 N 4Ceramic balls are used as friction pairs, the motor speed is 500r / min, the wear time is 30min, the test load is 10N, the test temperature is 800℃, and the friction radius is 1mm. The upper and lower planes of the wear sample are smooth and parallel, and the sample is ultrasonically cleaned before the test. After the experiment is completed, the MT-500 probe material surface wear scar measuring instrument is used to measure the surface cross-sectional profile and wear volume of the sample wear scar. Measure at three different positions of the wear scar, and then take the average value to obtain the wear rate of the sample.

[0036] The high temperature oxidation resistance test is carried out in a static, normal pressure, and atmospheric atmosphere according to the HB5258-2000 aviation industry standard. The test equipment uses a box-type resistance furnace. The prepared sample and substrate are gently polished on metallographic sandpaper to remove the edges and burrs, and their surface areas are measured. The sample is washed with ethanol solution and dried, and then left to stand for 1 hour, and the surface area is measured. At the same time, a clean crucible without residue is placed in a box-type resistance furnace and baked to constant weight at 800°C. The sample and substrate are placed in different crucibles, covered with crucible lids, and their original weights are weighed with a balance with an accuracy of 0.01mg. They are heated to 1000°C for high temperature oxidation for 24 hours, and weighed after air cooling. The oxidation weight gain per unit area of ​​the cladding layer is calculated. The less the weight gain after oxidation, the stronger its antioxidant ability and the longer its service life.

[0037] Example 1

[0038] The preparation method of applying a high temperature wear-resistant composite coating on the surface of H13 steel comprises the following steps:

[0039] Weigh 90g of Co-based stellite 6 alloy powder with a particle size of 50μm, 8.2g of TiCN powder with a particle size of 100nm, and 0.8g of Y 2 O 3 The powder was added to a ball mill and mixed for 2 hours, and then dried at 120 ° C in a vacuum environment for 1 hour to obtain a mixed powder for laser cladding ( Figure 1 shown).

[0040] Take a 40×40×20mm H13 steel alloy sample, grind its surface with 180-grit metallographic sandpaper, clean it with acetone to remove oil, wipe it clean, wipe it with alcohol, and blow it dry to obtain a pretreated titanium alloy matrix material. The surface-treated H13 steel sample is placed on the laser cladding workbench for use.

[0041] The laser cladding method with coaxial powder feeding is adopted. The prepared cladding powder is loaded into the powder chamber of the laser cladding device. The laser cladding process parameters are adjusted as follows: laser power 2000W, spot diameter 3.5mm, scanning speed 40mm / s, powder feeding rate 50g / min, overlap rate 50%, alloy powder carrier gas flow rate 15L / min. Under the irradiation of laser energy, a coating metallurgically bonded with the substrate is generated on the surface of H13 steel. The coating microstructure is shown in the figure below. Figure 2 As shown in Figure a, it can be seen that the organization is dense and regularly arranged. The wear rate test results are as follows Figure 3 As shown, the oxidation weight gain per unit area is Figure 4 shown.

[0042] Example 2

[0043] The preparation method of applying a high temperature wear-resistant composite coating on the surface of H13 steel comprises the following steps:

[0044] Weigh 89g of Co-based stellite 6 alloy powder with a particle size of 75μm, 10g of TiCN powder with a particle size of 100nm, and 0.5g of Y 2 O 3 The powder was added to a ball mill and mixed for 2 hours, and then dried at 120° C. in a vacuum environment for 1 hour to obtain a mixed powder for laser cladding. The H13 steel pretreated in Example 1 was taken as a substrate, and the mixed powder was clad on the substrate surface under the laser cladding parameter conditions of Example 1.

[0045] The coating test shows that the structure is dense and regularly arranged. The wear rate test results are as follows: Figure 3 As shown, the oxidation weight gain per unit area is Figure 4 shown.

[0046] Example 3

[0047] The preparation method of applying a high temperature wear-resistant composite coating on the surface of H13 steel comprises the following steps:

[0048] Weigh 89g of Co-based stellite 6 alloy powder with a particle size of 75μm, 10g of TiCN powder with a particle size of 100nm, and 0.5g of Y 2 O 3 The powder was added to a ball mill and mixed for 2 hours, and then dried at 120° C. in a vacuum environment for 1 hour to obtain a mixed powder for laser cladding. The H13 steel pretreated in Example 1 was taken as a substrate, and the mixed powder was clad on the substrate surface under the laser cladding parameter conditions of Example 1.

[0049] The coating test shows that the structure is dense and regularly arranged. The wear rate test results are as follows: Figure 3 As shown, the oxidation weight gain per unit area is Figure 4shown.

[0050] Comparative Example 1

[0051] The preparation method of applying a high temperature wear-resistant composite coating on the surface of H13 steel comprises the following steps:

[0052] The H13 steel pretreated in Example 1 was taken as a substrate, and stellite 6 alloy powder with a particle size of 75 μm was clad on the surface of the substrate under the laser cladding parameter conditions of Example 1.

[0053] The electron microscope image of the coating in Comparative Example 1 is as follows: Figure 2 As shown in Figure b, compared with the coating structure of Example 1, the grain size of the coating in Comparative Example 1 is significantly coarser and the structure arrangement is more chaotic. Figure 3 As shown, the oxidation weight gain per unit area is Figure 4 Its high temperature wear resistance and high temperature oxidation resistance are obviously inferior to those of Examples 1-3.

[0054] Comparative Example 2

[0055] The preparation method of applying a high temperature wear-resistant composite coating on the surface of H13 steel comprises the following steps:

[0056] 90 g of Co-based stellite 6 alloy powder with a particle size of 100 μm and 10 g of TiCN powder were weighed, added to a ball mill and mixed for 2 h, and then dried for 1 h in a vacuum environment at 120 ° C to obtain cladding powder for laser cladding. The H13 steel pretreated in Example 1 was taken as the substrate, and the mixed powder was clad on the substrate surface under the laser cladding parameter conditions of Example 1.

[0057] The wear rate test results are as follows: Figure 3 As shown, the oxidation weight gain per unit area is Figure 4 As shown. TiCN ceramic particles are added to the cladding powder of Comparative Example 2. Although the wear resistance of the coating is improved compared with Comparative Example 1, the high surface energy of the TiCN ceramic particles and the presence of macrosegregation at the junction greatly increase the cracking tendency of the coating and reduce the high temperature oxidation resistance of the coating. Its high temperature wear resistance and high temperature oxidation resistance are significantly inferior to those of Examples 1-3.

[0058] Comparative Example 3

[0059] The preparation method of applying a high temperature wear-resistant composite coating on the surface of H13 steel comprises the following steps:

[0060] Weigh 99g Co-based stellite 6 alloy powder with a particle size of 75μm, 0.8g Y 2 O 3The powder was added to a ball mill and mixed for 2 hours, and then dried at 120° C. in a vacuum environment for 1 hour to obtain a mixed powder for laser cladding. The H13 steel pretreated in Example 1 was taken as a substrate, and the mixed powder was clad on the substrate surface under the laser cladding parameter conditions of Example 1.

[0061] The wear rate test results are as follows: Figure 3 As shown, the oxidation weight gain per unit area is Figure 4 As shown. In the cladding powder of Comparative Example 3, stellite 6 alloy powder and Y 2 O 3 Rare earth powder, Y 2 O 3 Rare earth powder can purify the coating structure and improve some of the high-temperature oxidation resistance. However, due to the lack of hard phases at its grain boundaries and the lack of TiCN particles, the stellite 6 alloy powder has enough heat during laser processing to further grow the bonding phase metal γ-Co grains. The coating structure is relatively coarse, resulting in its high-temperature wear resistance being significantly inferior to that of Examples 1-3.

[0062] Comparative Example 4

[0063] The preparation method of applying a high temperature wear-resistant composite coating on the surface of H13 steel is similar to the steps of Example 1, except that the rare earth oxide is replaced by titanium carbide. When the rare earth oxide is replaced by titanium carbide, the high surface energy of titanium carbide aggravates the cracking sensitivity of the alloy during solidification, resulting in cracking of the coating.

[0064] Comparative Example 5

[0065] The method for preparing a high-temperature wear-resistant composite coating on the surface of H13 steel is similar to the steps of Example 1, except that the laser power parameter during the preparation process is 1500 W. Since the power for preparing the coating is too low, the coating fails to form a metallurgical bond with the substrate and falls off.

[0066] Comparative Example 6

[0067] The preparation method of applying high temperature wear-resistant composite coating on the surface of H13 steel is similar to the steps of Example 1, except that: 87g Co-based stellite6 alloy powder with a particle size of 50μm, 8.2g TiCN powder with a particle size of 100nm, 4.8g Y 2 O 3 Powder, excess Y in coating 2 O 3 Combined with the hard phase in the coating to form other compounds, resulting in a coarse coating structure and disordered arrangement (see Figure 5 b), while the coating prepared by the solution provided in the embodiment of the present invention has a dense structure and regular arrangement (see Figure 5(a in the middle), which reduces the high-temperature wear resistance and high-temperature oxidation resistance of the coating.

[0068] From the above experimental results, it can be seen that the present invention combines tellite6 alloy powder, TiCN ceramic powder, Re 2 O 3 Rare earth powders are mechanically mixed and then a metal-ceramic composite coating is prepared on the surface of the metal material by laser cladding technology. The Cr element in the stellite6 alloy powder in the metal-ceramic composite coating forms a dense Cr 2 O 3 The oxide film effectively prevents the problem of increased oxidation rate at high temperature. Nano-grade TiCN ceramic powder, Re 2 O 3 Rare earth powder can change the original coarse columnar crystals of the coating into fine equiaxed crystals, effectively controlling the generation of cracks and pores. 2 O 3 During the cladding process, M 7 C 3 Eutectic carbides precipitate and promote interfacial reactions around them, which causes other types of hard phases to precipitate, purify the coating and arrange the structure evenly. While reducing the tendency of the coating to crack, the high-temperature wear resistance and high-temperature oxidation resistance of the coating are further improved compared with other high-temperature resistant coatings. Compared with traditional processes, the preparation process is simple to operate, and the coating structure is relatively small and dense, which effectively reduces the cracking tendency of large-area cladding coatings while improving the high-temperature wear resistance of the coating.

[0069] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high temperature wear-resistant composite coating, characterized in that: The raw materials for preparing the high-temperature wear-resistant composite coating include, by weight percentage, 5%-10% TiCN powder and 0.3%-0.8% Re2O3 powder, with the remainder being metal powder. The microstructure of the high-temperature wear-resistant composite coating is as follows: a face-centered cubic γ-Co solid solution is used as a matrix phase, and intermetallic compounds Co3W, FeCo2, FeCo5, (Cr, Fe)7C3 and Cr3C2 and some elements Mo, W and Ni are dispersed in the matrix phase.

2. The high temperature wear-resistant composite coating according to claim 1, characterized in that: The Re in the Re2O3 powder includes one or more of Y, La, and Ce, and the metal powder is Stellite 6 powder.

3. The high temperature wear-resistant composite coating according to claim 2, characterized in that: The raw materials for preparing the high-temperature wear-resistant composite coating include, by weight percentage, 5%-10% of TiCN ceramic powder and 0.3%-0.8% of Y2O3 rare earth powder, and the remainder is stellite6 alloy powder.

4. The high temperature wear-resistant composite coating according to claim 3, characterized in that: The particle size of the stellite6 alloy powder is 45-105μm, and the chemical composition is as follows: C: 1.3%, Ni: 2%, W: 4.5%, Si: 0.8%, Mn: 0.5%, Mo: 1%, Fe: 2%, Cr: 29.7%, Co: balance; the particle size of the TiCN ceramic powder is 100-500nm, and the chemical composition is as follows: Fe: 0.1%, TiCN: balance; the particle size of the Y2O3 rare earth powder is 100-500nm, and the chemical composition is as follows: Fe2O3: 0.001%, Y2O3: balance.

5. A method for preparing a high temperature wear-resistant composite coating, characterized in that: It includes: A substrate is provided, and the high temperature wear-resistant composite coating according to any one of claims 1 to 4 is applied on the surface of the substrate.

6. The preparation method according to claim 5, characterized in that: A high-temperature wear-resistant composite coating is applied on the surface of the substrate by laser cladding, wherein: the laser power is controlled to be 2000-3500W, the scanning speed is 40-60mm / s, the overlap rate is 50-70%, the spot diameter is 3.5-4mm, the powder feeding rate is 35-50g / min, the protective gas flow rate is 13-20L / min, and the protective gas is preferably an inert gas.

7. The preparation method according to claim 5, characterized in that: The substrate is a metal material, including at least one of hot working die steel, cold working die steel, high speed tool steel, high chromium cast iron, stainless steel, heat resistant steel, wear-resistant and corrosion-resistant ferrous metal material, non-ferrous metal material, and self-fluxing alloy, preferably hot working die steel, and more preferably H13 steel.

8. The preparation method according to claim 5, characterized in that: The thickness of the high temperature wear-resistant composite coating is 1-2 mm.

9. A steel part, characterized in that: The high-temperature wear-resistant composite coating is obtained by laser cladding on the surface of a steel substrate using the preparation method described in any one of claims 5 to 8.

10. Use of the steel part according to claim 9 in preparing a hot forging die.